Motivational power of future time perspective: Meta-analyses in education, work, and health - Andre, Lucija; van Vianen, Annelies E. M.; Peetsma, Thea T. D.; Oort, Frans J. (PloS one, 2018)
Future time perspective (FTP) may predict individual attitudes and behaviors. However, FTP research includes different FTP conceptualizations and outcomes which hinder generalizing its findings. To solve the inconsistencies in FTP research and generalize the magnitude of FTP as a driver of motivation and behavior, we conducted the first systematical synthesis of FTP relationships in three crucial life domains. Our meta-analyses of FTP studies in education (k = 28), work (k = 17), and health (k = 32) involved N = 31,558 participants, and used a conceptual model for grouping FTP constructs. To address different outcome types, we applied the Theory of Planned Behavior when coding the studies. FTP relationships with outcomes were small-to-medium, were generalizable across domains, and were strongest when the FTP construct included a mixture of cognition, behavioral intention, and affect and, in education, when the FTP measure was domain specific rather than general. There were cross-cultural differences in FTP-outcome relationships. The strength of the FTP-outcome types relationship varied for attitudes, perceived behavioral control, behavioral intention, and behaviors. The lowest effect sizes were found for FTP predicting actual behaviors in education, work, and health and between FTP and health attitudes. Theoretical implications of the findings and future research directions are discussed.